Atrial Remodeling in Newly Diagnosed Drug‐Naive Hypertensive Subjects. Issue 6 (30th January 2013) - Aljizeeri, Ahmed; Gin, Kenneth; Barnes, Marion E.; Lee, Pui K.; Nair, Parvathy; Jue, John; Tsang, Teresa S. M.
Abstract : Background: Systemic hypertension is a major risk factor for heart disease and stroke. Data regarding temporal relationship of left atrial (LA) remodeling to onset of hypertension are sparse. We aimed to quantitate LA structural and functional remodeling in newly diagnosed hypertensive patients. Method: We prospectively identified 380 patients with newly diagnosed systemic hypertension naive to drug therapy, and 380 age‐matched control subjects without any history or evidence of hypertension. History or evidence of prior cardiovascular events, congenital or valvular heart disease, and renal dysfunction were exclusion criteria. Prevalence of LA enlargement, LA mechanical dysfunction expressed in total emptying fraction, left ventricular (LV) diastolic dysfunction, LV hypertrophy, and their interrelationships were assessed. Results: Of the 380 newly diagnosed hypertensive patients, 285 (75%) had LA enlargement, 308 (81%) had LA mechanical dysfunction, and 19 (5%) had LVH. Diastolic dysfunction was present in 334 (88%) of the patients. Compared to the controls, the hypertensive group had larger maximal, minimal, and pre‐A LA volumes (all P < 0.001). Total and active LA emptying fraction were significantly reduced (both P < 0.001). Total LA emptying fraction was strongly associated with systolic blood pressure [per 10 mmHg, HR 0.94 (0.89–0.98); P < 0.001], with stepwise decrease in LA emptying fraction of 6%, 10%, and 16% from the lowest (141–150 mmHg) to the top tertile of systolic blood pressure (>160 mmHg). Conclusion: In this drug‐naive cohort with newly diagnosed hypertension, LA structural and functional remodeling, and LV diastolic dysfunction were common findings prior to initiation of drug treatment. LVH was uncommon. Impairment of LA mechanical function was evident even in the mildly hypertensive subgroup.